KEKUASAAN PATRIARKI DALAM NOVEL NYUTRAYU KARYA JOKO GESANG SANTOSO - Brelian Wulan Sari; Indayani (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2026)
The purpose of this study is to describe the criticism of patriarchal power in the novel Nyutrayu by Joko Gesang Santoso. The study uses a qualitative descriptive approach. The study uses feminist theory, specifically viewing patriarchy as a structured social system operating within the realms of the household, paid work, the state, male violence against women, sexual relations, and culture. The novel Nyutrayu is the source of the data, which consists of quotations of narratives and dialogues that represent the practice of patriarchal dominance and criticism of it. The results of the study show that the novel Nyutrayu consistently presents criticism of the patriarchal system through the depiction of imbalances of power in households, the objectification and marginalization of women in the workplace, the state's failure to provide legal protection, the normalization of physical and sexual violence, control over women's bodies and sexuality, and cultural legitimization that supports male dominance. These critiques are conveyed not only through explicit acts of violence, but also through the internal reflections of female characters who recognize the structural injustices they experience.